Seni Mengelola Konflik Dalam Al-Qur’an: Kajian Atas Surah Al-Hujurat Ayat 9-10 - Makhsusiyah, Faizatul Munawaroh; Musolli (Universitas Yudharta Pasuruan, 2023)
Every human life, anytime and anywhere, will inevitably involve conflicts. These conflicts arise due to differences in opinions and feelings, cultural variations, interests, and social changes. These differences give rise to various conflicts worldwide, including political conflicts, racial conflicts, religious conflicts, mental conflicts, and more. In the Quran, there are broadly three types of conflicts, namely family conflicts, religious conflicts, and ethnic conflicts. Many of these conflicts are the stories of past communities with their prophets, from Prophet Adam to Prophet Muhammad. In every conflict narrated in the Quran, Allah hints at different ways of resolution, always concluding with guidance to settle disputes peacefully (ash-shulh), through consultation, negotiation, and other means. This emphasizes that no conflict is impossible if both parties have good intentions and goodwill. The ultimate goal is to achieve peace, justice, and harmony within society and among individuals. This research employs a library research method, which falls under content analysis. The author adopts a qualitative approach drawing from classical, medieval, and contemporary exegesis. The findings reveal that the interpretation of Surah Al-Hujurat verses 9-10 instructs two conflicting groups of believers to reconcile by seeking common ground toward a fair agreement. Allah also emphasizes that peace should take precedence in tumultuous conflicts.